Solving General Capacity Problem by Relaxed Cutting Plane Approach - Wu, Soon-Yi; Fang, Shu-Cherng; Lin, Chih-Jen (Annals of operations research, 2001)
This paper studies a class of infinite dimensional linear programming problems known as the general capacity problem. A relaxed cutting plane algorithm is proposed. A convergence proof together with some analysis of the results produced by the algorithm are given. A numerical example is also included to illustrate the computational procedure. [PUBLICATION ABSTRACT]